2012
DOI: 10.1037/a0024729
|View full text |Cite
|
Sign up to set email alerts
|

The role of source memory in older adults' recollective experience.

Abstract: Younger adults' "remember" judgments are accompanied by better memory for the source of an item than "know" judgments. Furthermore, remember judgments are not merely associated with better memory for individual source features but also with bound memory for multiple source features. However, older adults, independent of their subjective memory experience, are generally less likely to "bind" source features to an item and to each other in memory (i.e., the associative deficit). In two experiments, we tested whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 70 publications
2
39
1
Order By: Relevance
“…Research directly investigating conditional dependence between multiple context details suggests that young adults are more likely to bind multiple context features in memory, compared to older adults (Boywitt et al, 2012; Peterson & Naveh-Benjamin, 2016). In the current study, we found the opposite: older adults conditionally bound context details while younger adults did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research directly investigating conditional dependence between multiple context details suggests that young adults are more likely to bind multiple context features in memory, compared to older adults (Boywitt et al, 2012; Peterson & Naveh-Benjamin, 2016). In the current study, we found the opposite: older adults conditionally bound context details while younger adults did not.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in selective attention is suggestive of reduced inhibitory control (Hasher & Zacks, 1988). A reduced ability to selectively attend to a specific relationship may lead older adults to hyper-bind (Campbell, Hasher, & Thomas, 2010) and show a conditional dependence (Boywitt, Kuhlmann, & Meiser, 2012; Meiser, Sattler, & Weisser, 2008; Peterson & Naveh-Benjamin, 2016; Starns & Hicks, 2008) between relevant and irrelevant features during memory retrieval. A consequence of hyper-binding, in typical memory tasks, may be an impoverished memory representation for relevant contextual features.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the age-related difference in classification accuracy in parietal cortex during the See phase may reflect the well-established age-related deficit in representing or binding feature combinations (Boywitt, Kuhlmann, & Meiser, 2012; Chalfonte & Johnson, 1996; Li, Naveh-Benjamin, & Lindenberger, 2005; Mitchell et al, 2000; Naveh-Benjamin, 2000). The relatively weaker Think-phase category representations in temporal and occipital regions for older adults may then reflect this binding deficit—that is, because of a parietal-related binding deficit, features represented in temporal cortex are less likely to cue features represented in occipital cortex and/or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…According to the source monitoring framework (SMF, Johnson, Hashtroudi & Lindsay, 1993; Mitchell & Johnson, 2009), these less accurate memories are thought to arise from poor feature encoding and/or poor binding of features into cohesive representations of specific events (Boywitt, Kuhlmann, & Meiser, 2012; Chalfonte & Johnson, 1996; Li, Naveh-Benjamin, & Lindenberger, 2005; Mitchell, Johnson, Raye, Mather, & D’Esposito, 2000; Naveh-Benjamin, 2000) and from difficulty monitoring (reviving, evaluating) during remembering (Gallo, 2013; Mitchell et al, 2000, Experiment 2).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than being related to retrieving the conjoint features, the subjective experience of remembering in the patients seemed to be related recognition confidence. Hence, the parietal patients did not seem to be engaging in appropriate monitoring of the multidimensional representations they seemed able to retrieve-a kind of objective/subjective source memory dissociation (see Boywitt, Kuhlmann, & Meiser, 2012 for behavioral evidence of a similar dissociation in older adults). Together with other data in the literature, this seems to suggest that posterior parietal cortex is somehow involved in evaluating multidimensional information with respect to a subjective memorial experience or mapping the available objective information onto a subjective response.…”
Section: Subjective Experiencementioning
confidence: 99%